Depression and personality disorders among incarcerated offenders convicted of impulsive versus premeditated homicide - Jakubowska, Adrianna (The journal of forensic psychiatry & psychology, 2023)
Depression and personality disorders, such as Borderline Personality Disorder and Antisocial Personality Disorder, have been identified as common factors among homicide offenders. However, existing research often adopts a limited categorical approach and treats homicide offenders as a homogeneous group. In this study, we utilized a dimensional approach to investigate the differences in depression and personality disorders between impulsive and premeditated homicide offenders. A total of 83 homicide offenders, aged 20–74 (45 premeditated and 38 impulsive offenders), from two prisons in Poland participated in the study. They completed three questionnaires assessing depression and personality disorders using both categorical and dimensional approaches. No significant differences were found between the groups, suggesting that type of homicide alone should not guide clinical decision-making. However, premeditated homicide offenders demonstrated relatively higher levels of Detachment and Psychoticism, as well as above cut-off depressive symptoms. These findings tentatively suggest that the Psychoticism and Detachment domains may play an important role in premeditated homicide offenders. Considering the study’s limited sample size and utilization of abbreviated research instruments, a more comprehensive exploration in future studies using refined measures seems warranted. Moreover, the high prevalence of depressive symptoms as well as their associations with PD traits emphasizes the need for future studies to prioritize the investigation of depression within this group.